Penerapan Model Dragonfly Effect pada Instagram Sebagai Platform Kampanye HIV dan Kesehatan Seksual - Muaya, Gerald; Paramita, Sinta (Prologia, 2025)
According to data from the Indonesian Ministry of Health (2023), there are 526,841 people living with Human Immunodeficiency Virus (HIV). From this data, there are around 100,000 people who do not know their HIV status and have the potential to cause a wider spread without them realising it. This study aims to analyse the application of the Dragonfly Effect model on the @testJKT account in campaigning for HIV and sexual health issues, especially for Men who have Sexual Relations with Men (MSM) and transgender women through Instagram. This research uses a qualitative approach with a case study method and conducts observations, interviews, and documentation studies. The results of this study show that the campaign carried out by the @testJKT account can run effectively by coordinating and combining the four wings of the dragonfly effect, namely focus, grab attention, engage, and take action. TestJKT has the right purpose and focus according to the target audience, namely MSM and transgender women. The TestJKT account visualises its message purpose and focuses through creative graphic and audiovisual content, using the power of storytelling and touching the target audience personally so as to successfully stir the audience's emotions. In the end, the audience takes action easily and brings prosperity to themselves and the social community. Menurut data dari Kementerian Kesehatan RI (2023) terdapat 526.841 orang yang hidup dengan Human Immunodeficiency Virus (HIV). Dari data tersebut terdapat sekitar 100.000 orang yang belum mengetahui status HIV-nya dan berpotensi menimbulkan penyebaran yang lebih luas tanpa mereka sadari. Penelitian ini bertujuan untuk menganalisis penerapan model Dragonfly Effect pada akun @testJKT dalam mengkampanyekan isu HIV dan kesehatan seksual terutama bagi Lelaki yang melakukan hubungan Seksual dengan Lelaki (LSL) dan transgender perempuan melalui Instagram. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus serta melakukan observasi, wawancara, dan studi dokumentasi. Hasil dari penelitian ini menunjukkan bahwa kampanye yang dilakukan akun @testJKT dapat berjalan efektif dengan koordinasi dan memadukan empat sayap dragonfly effect yaitu focus, grab attention, engage, dan take action. TestJKT memiliki tujuan dan fokus yang tepat sesuai dengan target audiens yakni LSL dan transpuan. Akun TestJKT memvisualisasikan pesan, tujuan, dan fokusnya melalui konten grafis dan audiovisual yang kreatif, menggunakan kekuatan cerita dan menyentuh target audiens secara pribadi sehingga berhasil menggugah emosi audiens. Pada akhirnya, audiens mengambil aksi dengan mudah dan membawa kesejahteraan bagi dirinya dan masyarakat sosial.